The Effect Of Metformin On The Absorption Of Vitamin B12, Folic Acid, Homocysteine And Creatinin; A Cross-Sectional Study In Karbala Province - Karim, Anas; EYÜPOĞLU, Volkan (Journal of Neonatal Surgery, 2025)
Recent studies have related to estimate the effect of metformin and other anti-diabetic medication on the level of vitamin B12, folic acid, creatinin and homocysteine in patients with diabetes-mellitus type 2. This cross-sectional study will be accomplished over patients with different parameters including weight, age, body mass index, fasting blood glucose, HbA1c, duration of metformin usage, and the dosage of metformin. The results will be studied under light of control group. Samples size of 300 diabetic patients of type 2, with age ranged between 35-75 years, and a control group consisting of 30 healthy people will be collected from Karbala province/Iraq. As a result, the diabetic patients that taking metformin recorded higher value of homocysteine, and lower value was recorded in term of vitamin B12 and folate in comparison with patients on other antidiabetic drugs or patients on baseline (recently diagnosed). Also, there is not statistically differences in the term of (age, weight, BMI and creatinin) between the groups under studying, meanwhile a statistically differences were observed in term of HbA1c and fasting blood glucose between the investigated groups. Further, the results revealed that the duration and the dose of metformin have considerable impact over vitamin B12 deficiency deterioration. Objective: Investigating the effect of metformin and other antidiabetic drugs (OAD) on Vit B12, folic acid, fasting blood glucose (FBG), creatinin, glycated hemoglobin (HbA1c) and homocysteine in patients suffering from diabetes mellitus-type 2 Method: The present study was conducted over Karbala province/ Iraq as a cross sectional area of study. The duration of study is specified by the interval between the beginnings of April 2022 to the end of October 2022. The experimental tests were performed in private sector Laboratory. Result: the diabetic patients that taking metformin recorded higher value for homocysteine, and lower value was recorded for both vitamin B12 and folate in comparison with patients on other antidiabetic drugs or patients on baseline (recently diagnosed). Also, there is not statistically differences in the term of (age, weight, Body Mass Index (BMI) and creatinin) between the groups under studying, meanwhile a statistically differences were observed in term of HbA1c and fasting blood glucose between the investigated groups. Further, the results revealed that the duration and the dose of metformin have considerable impact over vitamin B12 deficiency deterioration. Conclusion: Patients with DM-type 2 on metformin have high level of Vit. B12 deficiency than patients didn’t used metformin or patient on other antidiabetic drugs also Dose and duration play an important role in Vit. B12 deficiency, as the duration and dose increase Vit. B12 deficiency increase.